Exclusive maternal breastfeeding and the Breastfeeding Self-efficacy Scale - Edficher Margotti; Matias Epifanio (Rev Rene)
This study aimed at determining the factors related to the duration of exclusive breastfeeding and to associate them to the scores of the Breastfeeding Self-efficacy Scale. 300 mother-baby binomials were studied, from the capital cities of the southern region of Brazil in 2012, using the Breastfeeding Self-efficacy Scale during postpartum period and with intervals from 15 to 120 days after delivery. The average of the score of breastfeeding was 36 points. The risk factors for breastfeeding were: hospitals which were not Child Friendly (p=0.002), schooling (≤ 8 years of study; p=0.004), and working mother (p=0.013). When evaluating the maternal breastfeeding after 120 days, the variables which were considered as protection factors  for breastfeeding were the maternal age of majority (p=0.039) and the score in the test of breastfeeding (p=0.046). The variables for the exclusive breastfeeding were the maternal age of majority and the score in the test of breastfeeding.